The Role of Tourist Satisfaction in The Relationship of Destination Image to The Loyalty of Tourists Visiting Coban Rondo Waterfall Tour - Alvianna, Stella; Hermawan, Hary; Hidayatullah, Sy; Aristanto, Eko (Media Wisata, 2023)
This study discusses destination image consisting of cognitive destination image (X1), unique destination image (X2) and affective destination image (X3) which are associated with visitor/tourist satisfaction (Y1) and loyalty (Y2). The type of research is explanatory research, while this research focuses on Coban Rondo tourist attractions in Malang Regency. The population of this research is all tourists/visitors at Coban Rondo tourist attractions, Malang Regency. the sample criteria used in this study were respondents at least 1 (once) time visiting CobanRondo  Waterfall with a sample size of 300 respondents. Questionnaires are distributed by visiting tourist destinations by providing a questionnaire link to visitors/tourists who are visiting CobanRondo. The collected questionnaires were then tabulated and analyzed using SPSS to determine the direct effect (multiple regression test of 2 models) and to determine the indirect effect by multiplying the direct effect of the path traversed. Results From the results of the analysis with the SPSS program and the previous discussion, it was found that the cognitive, unique and effective destination image variables directly affect tourist satisfaction and when viewed from a direct influence on loyalty also have an influence. Including the satisfaction-to-loyalty pathway also has an influential outcome. There is one path in this research that does not have an indirect effect, namely the influence between cognitive destination image and loyalty through satisfaction, which results in no indirect effect but directly this variable has an influence. While the unique and affective images directly or indirectly have influential results.